2014
DOI: 10.1111/bph.12430
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein quality control in health and disease

Abstract: Progressive mitochondrial dysfunction is linked with the onset of many age-related pathologies and neurological disorders. Mitochondrial damage can come in many forms and be induced by a variety of cellular insults. To preserve organelle function during biogenesis or times of stress, multiple surveillance systems work to ensure the persistence of a functional mitochondrial network. This review provides an overview of these processes, which collectively contribute to the maintenance of a healthy mitochondrial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 265 publications
(377 reference statements)
3
40
0
2
Order By: Relevance
“…The QC system links molecular, organellar, and cellular levels and includes (1) a protease/chaperone system (Voos, 2013); (2) mitochondrial fission and fusion processes (Twig et al, 2008;Osellame et al, 2012;Youle and van der Bliek, 2012;Elgass et al, 2013); and, in case the first two actions fail, (3) initiation of the intrinsic cell death program (Fischer et al, 2012;Gaspard and McMaster, 2015). It ensures the persistence of a healthy mitochondrial population and ultimately survival of the organism, especially during stress conditions (Baker et al, 2014).…”
mentioning
confidence: 99%
“…The QC system links molecular, organellar, and cellular levels and includes (1) a protease/chaperone system (Voos, 2013); (2) mitochondrial fission and fusion processes (Twig et al, 2008;Osellame et al, 2012;Youle and van der Bliek, 2012;Elgass et al, 2013); and, in case the first two actions fail, (3) initiation of the intrinsic cell death program (Fischer et al, 2012;Gaspard and McMaster, 2015). It ensures the persistence of a healthy mitochondrial population and ultimately survival of the organism, especially during stress conditions (Baker et al, 2014).…”
mentioning
confidence: 99%
“…As such, the mechanisms that regulate mitochondrial quality control are receiving increased attention. These mechanisms include resident mitochondrial chaperones and proteases that help re-fold or degrade misfolded mitochondrial proteins, as well as the process of fusion and fission, that seems essential to maintain mitochondrial homeostasis (Baker et al, 2014; Burte et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, autoimmune responses against cardiac antigens are believed to mediate the development of DCM, as sera from DCM patients have been shown to contain autoantibodies for cardiac antigens, such as cardiac myosin, and cardiac troponin-I (cTnI) [3][4][5][6][7]. Recently, we demonstrated that the mitochondrial inner membrane protein, adenine nucleotide translocator 1 (ANT 1 ) can be a target autoantigen in the pathogenesis of DCM by identifying ANT 1 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] as the disease-inducing epitope in A/J mice [2]. In this report, we describe the potential relevance of the mitochondrial matrix branched chain a-ketoacid dehydrogenase (BCKD) complex proteins to myocarditis and hepatitis.…”
Section: Introductionmentioning
confidence: 99%